Laparoscopic Incisional Hernia Repair With Fibrin Glue in Select Patients - Stefano, Olmi (Society of Laparoendoscopic Surgeons, 2010)
BACKGROUND AND OBJECTIVE: Laparoscopic treatment of incisional hernias can be performed using different types of fixation devices and prosthesis. We present a case series of 19 patients with incisional hernias with a diameter of <6cm, who underwent laparoscopic repair using Hi-tex dual-side mesh, positioned intraperitoneally, fixed to the abdominal wall by fibrin glue (Tissucol). METHODS: Nineteen patients with incisional hernias <6cm in diameter were enrolled in this study and treated laparoscopically with Hi-tex and Tissucol. Surgical complications and patient outcomes were assessed with a clinical follow-up. RESULTS: Laparoscopic repair of incisional hernias by using Hi-tex mesh affixed to the parietal wall with fibrin glue was feasible and easy in patients with parietal defects <6cm in diameter. Mean operating time was 30 minutes. Mean hospital stay was 1.5 days. Almost no postoperative pain, major surgical complications, seroma formation, relapses, or prosthesis infection occurred during a mean follow-up of 20 months. CONCLUSIONS: In select patients, Hi-tex mesh affixed using fibrin glue allows laparoscopic repair of incisional hernias with very good patient outcomes, especially in terms of postoperative pain and seroma formation.